Electrochemical corrosion behaviour of Sn-Sb solder alloys: the roles of alloy Sb content and type of intermetallic compound - Dias, Marcelino; Verissimo, Nathalia C.; Regone, Natal N. [UNESP]; Freitas, Emmanuelle S.; Cheung, Noe; Garcia, Amauri (Taylor & Francis Ltd, 2020)
Sn-Sb solder alloys (2; 5.5 and 10wt-% Sb) were directionally solidified with a view to permitting the effect of a wide range of solidification cooling rates to be related to the resulting microstructure, which is shown to be formed by a cellular Sn-rich matrix with Sn-Sb intermetallic particles (IMCs) randomly distributed in the matrix The corrosion resistance of these alloys is investigated by electrochemical impedance spectroscopy (EIS), equivalent circuit and linear polarisation and the results correlated with microstructural features. The increase in the alloy Sb content is shown to change the nature/morphology of the Sn-Sb IMCs, consequently affecting the corrosion resistance. The EIS data indicated that the Sn-10wt-%Sb alloy has the best corrosion resistance because of the high resistance of its oxide barrier layer. The polarisation curves also indicate lowest corrosion rate and nobler potential related to the Sn-10wt-%Sb alloy, which has also been confirmed by calculations of polarisation resistance.
Keywords: Solder alloys; Sn-Sb alloys; microstructure; corrosion resistance